Long term histological improvement and clearance of intrahepatic hepatitis C virus RNA following sustained response to interferon-ribavirin combination therapy in liver transplanted patients with hepatitis C virus recurrence. Issue 2 (1st February 2003) - Bizollon, T; Ahmed, S N S; Radenne, S; Chevallier, M; Chevallier, P; Parvaz, P; Guichard, S; Ducerf, C; Baulieux, J; Zoulim, F; Trepo, C
Abstract : Background and objective: A proportion of liver transplanted patients with recurrent chronic hepatitis have a sustained virological response to combination therapy with interferon plus ribavirin. However, the long term benefit of antiviral therapy with regard to hepatitis C virus (HCV) RNA clearance remains unknown in patients with HCV recurrence. This study examined the long term biochemical, virological, and histological outcome in transplanted patients with recurrent chronic hepatitis who had a sustained virological response to antiviral therapy. Patients and methods: Fifty four patients with recurrent hepatitis C were treated with antiviral therapy involving induction by combination therapy (interferon (IFN) plus ribavirin) for six months and maintenance ribavirin therapy for 12 months. Fourteen patients who had recurrent chronic hepatitis and sustained virological response to antiviral therapy were followed for three years after the end of antiviral therapy. Serum alanine aminotransferases were assessed every three months during the observation period. Serum hepatitis C RNA detected by polymerase chain reaction was evaluated every six months during follow up, and protocol biopsy procedures were performed routinely every year. Semiquantitative histopathological assessment of allograft hepatitis was performed using the Knodell score and HCV was also detected by polymerase chain reaction on frozen graft tissue samples. Results: At the end of antiviral therapy, the sustained response rate was 26%. A complete response (normal serum alanine aminotransferase level and undetectable serum HCV RNA) was achieved in 13/14 (93%) patients three years after the end of treatment. A comparison of liver histology findings before and after a mean of three years after antiviral therapy showed a clear improvement in 12/14 (86%) patients. In 5/14 (36%) patients, the last biopsy showed normal or near normal histological findings. After three years of follow up, the total Knodell score was 3.2 (range 1–8) versus 8.3 (range 5–12) before treatment (p=0.001). Graft HCV RNA was detectable before treatment in all 14 patients and was undetectable at the end of follow up in 13/14 (93%) patients tested. Conclusion: In patients with biochemical and virological responses induced by ribavirin and interferon, a complete response was sustained in 93% for at least three years after cessation of therapy. This long term response was associated with absence of detectable intrahepatic hepatitis C RNA and marked histological improvement.